Doskonalenie controllingu poprzez systematyczną ocenę jego stosowania w przedsiębiorstwie - Nowosielski, Krzysztof (Controlling improvement through systematic assessment of its functioning in an enterprise, 2006)
The paper presents the essence of controlling assessment. The scheme of assessment system of controlling was showed included main elements. The role of controlling as evaluated object and mensuration subsystem was explained in details. The possible ways of results usage in controlling improvement were also indicated.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1125, s. 81-88